Evaluation of the Effectiveness of Mobile Health Apps in Improving Public Health Awareness in Indonesia - Andi Muhammad Multazam; Yenik Pujowati; Suryani Hartati (West Science Information System and Technology, 2024)
This study investigates the effectiveness of mobile health apps in enhancing public health awareness in Indonesia through a quantitative analysis. Using 170 participants, data was collected through surveys to assess mobile health app usage patterns and public health awareness levels. Results indicate that frequent use of mobile health apps is positively associated with higher public health awareness scores. Specifically, fitness tracking and nutrition apps were found to be significantly correlated with increased public health awareness. These findings highlight the potential of mobile health apps as tools for disseminating health information and empowering individuals to make informed decisions about their health. The study contributes to understanding the role of mobile technology in promoting public health awareness in Indonesia and underscores the importance of targeted interventions tailored to specific health needs and preferences.